Performance of profiled steel sheet dry board system under flexural bending and vibration - Ehsan, Ahmed (Universiti Malaysia Sarawak (UNIMAS), 2011)
This paper describe the experimental performance of Profiled Steel Sheet Dry Board system (PSSDB) against out-of plane bending and vibration. This paper focus on theoretical and experimental procedures to determine the overall performance of PSSDB system against vibration and flexural will be discussed in this paper.